Educação informal e anticomunismo: a iconografia política durante a Era Vargas (1930 – 1945) - Bona, Gabriela Cristina Beltramin De (2020)
This research analyzes the relationship between the anti-communist movement of the Vargas Era (1930 to 1945) and informal education, based on the political iconographies published in the period. These documents were listed from periodic sources, mainly from integralist newspapers, such as A Offensiva, Acção and Anauê!, and also from bibliographic sources, by authors such as Motta (2002) and Fiorucci (2016). The bibliographic research comprised authors who turned their attention to the anti-communist movement, such as Dutra (2012), Carneiro (2002) and Capelato (1998), in addition to the authors who supported the historical context such as Fausto (1995), Romanelli (1986) and Hobsbawm (1995). It also aimed to promote the analysis of the images broadcast during the period, addressing their techniques of convincing from the elements present in them, their nuances and their reach in society at the time. Authors like Cardoso and Vainfas (2012), Bakhtin (2006) and Gasca and Gubern (2011) contributed to the analysis of iconographic language. These images had a formative character in the social imaginary, reaching a significant part of the population, even the illiterate, for having elements of easy abstraction, although it had components that went beyond the perception given at first sight. Such imagery resources contribute indirectly to an educational formation, even though they are not inserted in the formal / school educational scope. Therefore, through the concept of informal education, the relationship between the iconographic circulation produced by the press in the Vargas period and the informal education process was established.